Números complexos: um estudo de aplicações a trigonometria e as equações algébricas - Araújo, Adenildo Texeira de (2014)
The study of the complex numbers in the medium teaching is characterized, almost exclusively, for the algebraic approach leaving the geometric part and their applications without a due importance. This work presents a study on complex numbers as well as some of their applications so much of the algebraic part, applied to polynomials, as of the geometric part especially applied to the trigonometry. Of I begin did an approach of the historical facts of those numbers mentioning some mathematical that gave their contributions near of that complex group. Soon afterwards the part theoretical, algebraic and geometric is presented, as well as some applications the trigonometry. Finally we presented the theory of the quadratic and cubic algebraic equations and the interaction of those with the complex numbers.